2012
DOI: 10.1017/s0031182011002411
|View full text |Cite
|
Sign up to set email alerts
|

The development of Psychodiella sergenti (Apicomplexa: Eugregarinorida) in Phlebotomus sergenti (Diptera: Psychodidae)

Abstract: SUMMARYPsychodiella sergenti is a recently described specific pathogen of the sand fly Phlebotomus sergenti, the main vector of Leishmania tropica. The aim of this study was to examine the life cycle of Ps. sergenti in various developmental stages of the sand fly host. The microscopical methods used include scanning electron microscopy, transmission electron microscopy and light microscopy of native preparations and histological sections stained with periodic acid-Schiff reaction. Psychodiella sergenti oocysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
10
0
2
Order By: Relevance
“…sergenti is harmful to its host Ph. sergenti under laboratory conditions and that the parasite's effects can be influenced by environmental factors (Lantova et al ). Furthermore, the severity of a gregarine infection ( Ascogregarina culicis ) on its natural host ( Aedes aegypti ) was shown to vary both among four different geographic origins of the parasite and among three different populations of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…sergenti is harmful to its host Ph. sergenti under laboratory conditions and that the parasite's effects can be influenced by environmental factors (Lantova et al ). Furthermore, the severity of a gregarine infection ( Ascogregarina culicis ) on its natural host ( Aedes aegypti ) was shown to vary both among four different geographic origins of the parasite and among three different populations of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The effects range from high mortalities in ascidians [28] to negligible effects in bivalves [30]. In vitro experiments in insects have suggested that the number of gregarines can affect, for example, the overall flight performance and mating success of dragonflies [31], increase adult mortality and inhibit ovarian and fat body development in the western corn rootworm [32], mortality of immature sand fly stages and a negative effect on the survival of adult males and females [33]. Due to these negative effects on hosts that can be either disease vectors or pests, the potential of gregarines as biological control agents has been discussed [33,34], but their usefulness is often questioned by the authors.…”
Section: What Is the Actual Life Strategy Of Gregarines?mentioning
confidence: 99%
“…Therefore, nutritional depletion might result in size and weight reduction, as observed in the larvae of beetles Dermestes maculatus (Lord and Omoto, 2012) and Tenebrio molitor (Harry, 1967). Furthermore, the physiological processes of the host, including reproduction and development, might be compromised (Bouwma et al, 2005;Er and Gokce, 2005;Harry, 1970;Lange and Lord, 2011;Lantova et al, 2011;Lord and Omoto, 2012;Schreurs and Janovy, 2008), and eventually lead to its death (Harry, 1967;Valigurová, 2012).…”
Section: Q2mentioning
confidence: 99%